Flora of the indian desert jodhpur and jaisalmer reprinted from The journal of the bombay natural histroy society - Blater, E.; Hallberg, F. (Jodhpur Scientific Pub., 1984)
with 74 photographs
Reprinted from The journal of the Bombay natural history society, v. 26-27
Keywords: Desert flora -- India -- Jodhpur; Desert flora -- India Jaisalmer; Botany